Ovarian Torsion: Presentation and Management in a Pediatric Patient - Katie P. Nguyen; William L. Valentino; Duy Bui; Honey Milestone (Case Reports in Obstetrics and Gynecology)
Background. Adnexal torsion is the fifth most common gynecologic emergency accounting for approximately 20 to 30% of ovarian surgeries in pediatric patients. Case. The patient is a ten-year-old female who presented to the emergency room for severe left lower quadrant abdominal pain. On presentation, she was hemodynamically stable with an acute abdomen. A transabdominal ultrasound showed a predominantly anechoic structure measuring up to 5.6 cm without definitive Doppler flow, concerning for a large cyst causing ovarian torsion. Gynecology was consulted, and the patient underwent a diagnostic laparoscopy, aspiration of the left ovarian cyst, and left ovarian detorsion. Pathology results were consistent with benign cystic contents. Conclusion. Appropriate diagnosis and timely surgical gynecological intervention allowed this pediatric patient to salvage and preserve ovarian function.